Analisis Pertimbangan Hukum Hakim PTUN Terhadap Keputusan tentang Pergantian Antarwaktu Anggota Legislatif (Studi Putusan Nomor 05/G/2011/PTUN.YK) - Abdul Jamil; Sufriadi (Faculty of Law Universitas Lancang Kuning, 2020)
This study aimed to examine two objectives: first, legal considerations of court decision Number 05/G/2011/PTUN.Yk regarding state administrative decision on intermittent termination and replacement (PAW) a member of the Bantul Regional Representative Council (DPRD), and second, panel of judges rationale concluded that the decision on PAW was not absolute competence of PTUN. This research is classified as normative legal research using both primary data by conducting interviews with PTUN judges and the expert, and secondary data in the form of legal material. The results showed: first, there are three main legal considerations used by judges: 1. the decision on PAW is a decision in the field of politics and constitutionality; 2. the decision on PAW does not fullfil the unilateral will element; 3. the existence of jurisprudence. Second, the judge's judgments rested on the conclusion that the decision did not fulfill the 'state administration' element and was emphasized in the 'initial process' of the PAW stage series, not to the 'final process' in the form of issuing decisions. The judgments put forward the interpretation based on doctrine, while if compared with the provisions of the Law on Administrative Court, the decision on PAW had actually been fulfilled as the KTUN which was the absolute competence of PTUN.